Growth Impairment of Small-Cell Cancer by Targeting Pro-Vasopressin with MAG-1 Antibody - North, William G.; Akerman, Bonnie L.; Cole, Bernard F.; Pang, Roy H. (Frontiers in Oncology, 2014)
Abstract Previously we demonstrated that human small-cell lung cancer (SCLC) seems to universally express the vasopressin gene, and this leads to the presence of a cell-surface marker representing the entire prohormone precursor. In this study we show this marker can be targeted with MAG-1, a mouse monoclonal antibody against a C-terminal moiety on provasopressin. In vitro targeting of cell lines derived from primary and recurrent disease demonstrates attachment of antibody to the cell surface followed by internalization. In vivo targeting with 99Tc-labeled Fab fragments of MAG-1 shows selective attachment to xenografts. In vivo treatment of tumors from classical cell line, NCI H345, with either ~1.65 µCi (~1.65 mg)/kg bw of 90 Yttrium-labeled MAG-1, or ~1.65 mg/kg bw native MAG-1, delivered every second day for 6 days produced similar reductions in the growth rate to ~50% (p